Impact of moderate-to-late preterm birth on neurodevelopmental outcomes in young children: Results from retrospective longitudinal follow-up with nationally representative data - Lee, Sangmi; Han, Yuri; Lim, Min Kyung; Lee, Hun Jae (PLOS ONE, 2023)
This study investigated the relationship between moderate-to-late preterm (MLPT) birth and the risk of neurodevelopmental impairments (NIs) in young children compared with the risks associated with very preterm (VPT) and full-term (FT) birth based on nationally representative large-scale population data. Retrospective follow-up was conducted over 71 months for 738,733 children who were born and participated in the Korean National Health Screening Program for Infants and Children (NHSPIC) between 2011 and 2013. Using a data linkage between the NHSPIC and Korean healthcare claim information, data on birth year, sex, delivery type, birth weight, growth abnormality, gestational age, breastfeeding history, maternal age, NIs, multiple gestation, preterm labor, premature rupture of membranes (PROM), gestational diabetes, gestational hypertension, smoking during pregnancy, and socioeconomic status were collected and included in the final analysis. Cox proportional hazards models were applied to identify the impact of gestational age on NI risk, with all variables adjusted as appropriate. Overall, 0.9% and 3.8% rates of VPT and MLPT births were identified, respectively. NI incidence was highest among VPT children (34.7%), followed by MLPT (23.9%) and FT (18.2%) children. Both VPT (hazard ratio [HR], 1.45; 95% confidence interval [CI], 1.03 to 2.05) and MLPT (HR, 1.21; 95% CI, 1.04 to 1.41) births were associated with increased NI risk. Low birth weight, PROM, and smoking during pregnancy were also associated with increased NI risk, while longer breastfeeding and higher socioeconomic status were associated with decreased risk. Special attention must be given to NIs for both VPT and MLPT children.